2008
DOI: 10.1007/s00702-007-0865-7
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in visuo-spatial working memory, inhibition and oculomotor control in boys with ADHD and their non-affected brothers

Abstract: Summary. Few studies have assessed visuo-spatial working memory and inhibition in attention-deficit=hyperactivity disorder (ADHD) by recording saccades and consequently little additional knowledge has been gathered on oculomotor functioning in ADHD. Moreover, this is the first study to report the performance of non-affected siblings of children with ADHD, which may shed light on the familiality of deficits. A total of 14 boys with ADHD, 18 non-affected brothers, and 15 control boys aged 7-14 years, were admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 68 publications
4
39
0
2
Order By: Relevance
“…In this regard, Brocki, Rendall, Bohlin, and Kerns (2008) imply a higher deficit in phonological WM in ADHD, as previous studies suggest ( . However, other studies hint that the deficiencies lie in the visuospatial WM (Martinussen et al, 2005;McInnes, Humphries, HoggJohnson, & Tannock, 2003;Rapport et al, 2008;Rommelse et al, 2008;Westerberg, Hirvikoski, Forssberg, & Klingberg, 2004;Willcutt et al, 2005). A third group of investigations point at a more generalised WM decay, a central executive deficit Dovis, Van der Oord, Wiers, & Prins, 2013;Nyman et al, 2010;van Ewijk et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Brocki, Rendall, Bohlin, and Kerns (2008) imply a higher deficit in phonological WM in ADHD, as previous studies suggest ( . However, other studies hint that the deficiencies lie in the visuospatial WM (Martinussen et al, 2005;McInnes, Humphries, HoggJohnson, & Tannock, 2003;Rapport et al, 2008;Rommelse et al, 2008;Westerberg, Hirvikoski, Forssberg, & Klingberg, 2004;Willcutt et al, 2005). A third group of investigations point at a more generalised WM decay, a central executive deficit Dovis, Van der Oord, Wiers, & Prins, 2013;Nyman et al, 2010;van Ewijk et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The main focus of neuroimaging and neuropsychological ADHD research is on higher cognitive functions although there is some evidence for disturbance of more basal functions such as speed of information processing [4] , motor function [5] , and olfactory functioning [6][7][8][9] . Recently we found improved odour sensitivity in children with ADHD [9] .…”
mentioning
confidence: 99%
“…After a certain delay, the participant then has to execute a saccade to the memorized location. In this task, the interval is longer than the interval in the present study (250 ms vs. 3,000 ms; e.g., Rommelse, Van der Stigchel, Witlox, et al, 2008). It is therefore possible that the use of a longer interval might have resulted in a difference between the patient and the control group.…”
Section: Discussionmentioning
confidence: 60%
“…Although this type of error has been linked to failures in oculomotor inhibition (Mostofsky, Lasker, Cutting, Denckla, & Zee, 2001;Rommelse, Van der Stigchel, Witlox, et al, 2008), these findings have been observed in a different task from the one current employed-namely, the memoryguided saccade task. In this task, the participant is not allowed to make a saccade towards the target but has to remember the location of the target.…”
Section: Discussionmentioning
confidence: 74%